Starch Production in Chlamydomonas reinhardtii through Supraoptimal Temperature in a Pilot-Scale Photobioreactor - Ivanov, Ivan N; Zachleder, Vilém; Vítová, Milada; Barbosa, Maria J; Bišová, Kateřina (Cells, 2021)
An increase in temperature can have a profound effect on the cell cycle and cell division in green algae, whereas growth and the synthesis of energy storage compounds are less influenced. In Chlamydomonas reinhardtii, laboratory experiments have shown that exposure to a supraoptimal temperature (39 °C) causes a complete block of nuclear and cellular division accompanied by an increased accumulation of starch. In this work we explore the potential of supraoptimal temperature as a method to promote starch production in C. reinhardtii in a pilot-scale photobioreactor. The method was successfully applied and resulted in an almost 3-fold increase in the starch content of C. reinhardtii dry matter. Moreover, a maximum starch content at the supraoptimal temperature was reached within 1-2 days, compared with 5 days for the control culture at the optimal temperature (30 °C). Therefore, supraoptimal temperature treatment promotes rapid starch accumulation and suggests a viable alternative to other starch-inducing methods, such as nutrient depletion. Nevertheless, technical challenges, such as bioreactor design and light availability within the culture, still need to be dealt with.
Keywords: teplota; bioreaktory; Starch; kultivační média; Bioreactors; Cell Cycle; biomasa; Culture Media; Photobioreactors; světlo; fotobioreaktory; průmyslová mikrobiologie; Chlamydomonas reinhardtii; Biomass; Light; mikrořasy; Microalgae; Industrial Microbiology; buněčný cyklus; škrob; Temperature